Knowledge Design: A Much Needed Discipline (Nóema, 2016)
In the age of print, the disposition and density of words on the page conveyed specific messages about how texts were supposed to be read. In the current proliferation of electronic supports, “knowledge design” is required to make sure that the process of passing on information becomes an effective transfer of knowledge. The article addresses the cohabitation of print environment and digital environment with reference to the recent debate on the digitization of learning and the so-called “digital colonialism.” The bi-dimensionality of tablets and e-book readers vs. the tri-dimensionality of books and reactions from intellectuals to digital reading and learning are also addressed. Teachers in the age of over-(and dis-)information are now assigned the role of “cultural djs.” A reappraisal of ancient rhetoric in its classic three-part subdivision is therefore needed: invention (knowledge creation), disposition (knowledge design), and elocution (knowledge management).
Keywords: David Bowie; Roberto Casati; Bill Gates; digital; Steve Jobs; Marshall McLuhan; Plato; print; rhetorics; Jacques Rancière; Slavoj Žižek